Effects of Cardiac Rehabilitation Training in Patients with Heart Failure Based on Traditional Chinese Exercise: A Systematic Review and Meta-Analysis. (15th November 2021) - Yao, Fang; Zhang, Yang; Kuang, Xiaohong; Zhou, Qi; Huang, Lihua; Peng, Jiazhu; Hou, Kun; Du, Shizheng
Abstract : Background and Objective . Traditional Chinese exercise (TCE) includes a variety of training methods. At present, more researchers focus the TCE as an alternative therapy of exercise rehabilitation in patients with heart failure (HF). Although studies show that TCE is considered a new approach in cardiac rehabilitation, the method has not yet been included in the domestic and international guidelines for managing HF, suggesting that the efficacy of TCE needs to be further explored. Currently, no systematic review or meta-analysis has been conducted to assess the effects of TCE-based cardiac rehabilitation training in patients with HF. In order to address this knowledge gap, this meta-analysis aimed to systematically evaluate the effects of cardiac rehabilitation training using the TCE on motor function, heart function, and quality of life in patients with HF. Methods . PubMed, Embase, Cochrane Library, and three Chinese databases, namely, China National Knowledge Network, Wanfang, and China Biomedical Network, were searched from the time of their inceptions through August, 2021. We retrieved the studies on the application of TCE-based cardiac rehabilitation in patients with HF. Based on the standard evaluation methods of Cochrane Reviewer's Handbook 5.1.0, two authors independently assessed the risk of bias and evaluated the methodological quality of the studies included. The RevMan 5.3 software was used for further meta-analysis. Additionally, the GRADEpro GDT web version was used to assess the quality of the evidence in these studies. Results . Nine randomized controlled trials involving 721 patients were included in this analysis. The meta-analysis revealed that the TCE (experimental group) effectively improved the patient's motor function and endurance compared to walking or other activities (control group) (mean difference, MD = 68.23, 95% CI [54.55, 81.91]; P < 0.00001 ). From each subgroup analysis, the exercising ability of the experimental group was higher than that of the control group. The quality of life's score in the experimental group was lower than that of the control group (MD = −9.51, 95%CI [−17.84, −1.18]; P = 0.03 ). The plasma B-type natriuretic peptide content in the experimental group was lower than that in the control group (MD = −59.77, 95%CI [−82.85, −36.7]; P < 0.00001 ). The number of hospitalizations (MD = −0.83, 95%CI [−0.98, −0.68]; P < 0.00001 ) and hospital costs in the experimental group (MD = −1.6, 95%CI [−1.89, −1.31]; P < 0.00001 ) were lower than those in the control group. However, no significant differences were observed in the left ventricular ejection fraction and maximal oxygen consumption between the two groups (MD = 1.38, 95%CI [−3.08, 5.84] and P = 0.54 ; MD = −0.04, 95%CI [−1.62, 1.54] and P = 0.96, respectively). From the current analysis, TCE can be considered a relatively safe exercise method. According to the GRADE evaluation results on the evidence level, the studies included were of moderate quality, low quality, or very low quality. Conclusions . Our systematic review showed that TCE had potential benefits in improving patients' cardiac function, motor function, and quality of life. Therefore, TCE might be an effective adjuvant therapy in patients with HF. However, given the inclusion of the low-quality elucidations, further rigorous studies are urgently needed to confirm these results.